To the study of 10D100 diesel engines of operating diesel locomotives by the fuel supply advance angle - Ablyalimov O. (E3S Web of Conferences, 2023)
The results of the justification for the distribution of diesel engines 10D100 are presented, taking into account the value of the actual advance angle of fuel supply at the nominal operating mode of the diesel generator set of operating diesel locomotives. A methodology for studying the dynamics of changes in the empirical and theoretical distribution of quantities is proposed, lean on the basic principles of probability theory and mathematical statistics, taking into account the criteria of agreement of Pearson and A. N. Kolmogorov's. It has been proven that the distribution of the studied diesel locomotive diesel engines according to the actual fuel supply advance angle corresponds to the law of normal distribution. It is recommended to continue these studies for partial load conditions, covering a larger number of operating diesel locomotives on railway sections of different complexity.